Inorganic Nanotubes and Fullerene-like Nanoparticles at the Crossroads between Solid-State Chemistry and Nanotechnology - Višić, Bojana; Panchakarla, Leela Srinivas; Tenne, Reshef (Journal of the American Chemical Society, 2017)
Inorganic nanotubes (NTs) and fullerene-like nanoparticles (NPs) of WS2 were discovered some 25 years ago and are produced now on a commercial scale for various applications. This Perspective provides a brief description of recent progress in this scientific discipline. The conceptual evolution leading to the discovery of these NTs and NPs is briefly discussed. Subsequently, recent progress in the synthesis of such NPs from a variety of inorganic compounds with layered (2D) structure is described. In particular, we discuss the synthesis of NTs from chalcogenide- and oxide-based ternary misfit layered compounds, as well as their structure and different growth mechanisms. Next we deliberate on the mechanical, optical, electrical, and electromechanical properties, which delineate them from their bulk counterparts and also from their graphene-like analogues. Here, different experiments with individual NTs coupled with first-principles and molecular dynamics calculations demonstrate the unique physical nature of these quasi-1D nanostructures. Finally, the various applications of the fullerene-like NPs of WS2 and NTs formed therefrom are deliberated. Foremost among the possibilities are their extensive uses as superior solid lubricants. Combined with their nontoxicity and their facile dispersion, these NTs, with an ultimate strength of about 20 GPa, are likely to find numerous applications in reinforcing polymers, adhesives, textiles, medical devices, metallic alloys, and even concrete. Other potential applications in energy-harvesting and catalysis are discussed in brief.